Multiple ecosystem service synergies and landscape mediation of biodiversity within urban agroecosystems. (23rd January 2023) - Jha, Shalene; Egerer, Monika; Bichier, Peter; Cohen, Hamutahl; Liere, Heidi; Lin, Brenda; Lucatero, Azucena; Philpott, Stacy M.
Abstract: Ecosystem services (ESs) are essential for human well‐being, especially in urban areas where 60% of the global population will live by 2030. While urban habitats have the potential to support biodiversity and ES, few studies have quantified the impact of local and landscape management across a diverse suite of services. We leverage 5 years of data (>5000 observations) across a network of urban community gardens to determine the drivers of biodiversity and ES trade‐offs and synergies. We found multiple synergies and few trade‐offs, contrasting previous assumptions that food production is at odds with biodiversity. Furthermore, we show that natural landscape cover interacts with local management to mediate services provided by mobile animals, specifically pest control and pollination. By quantifying the factors that support a diverse suite of ES, we highlight the critical role of garden management and urban planning for optimizing biodiversity and human benefit. Abstract : We leverage 5 years of data (>5000 observations) across a network of urban community gardens to determine the drivers of biodiversity and ecosystem service trade‐offs and synergies. We found multiple synergies and few trade‐offs, contrasting previous assumptions that food production is at odds with biodiversity. By quantifying the factors that support a diverse suite of ecosystem services, we highlight the critical role of garden management and urban planning for optimizing biodiversity and human benefit.